PENGARUH PELAYANAN, SANKSI KETERLAMBATAN PEMBAYARAN PAJAK DAN PELAPORAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM YANG MENGGUNAKAN SAK ETAP DI BATAM - Raja Hamizah Eka Putri; Gusnardi '; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is to knowing the effect of tax services, penalties of delay payments, and penalties of delay tax reporting to the obedience of micro, small and medium enterprise taxpayers using SAK ETAP. The techniques of data collection were used closed questionnaires. Total of population in this research are 68 UMKM Taxpayers using SAK ETAP. In determining the number of samples, researchers used the method of saturation sampling, so the number of samples totaling 68 Taxpayers. The collected data is then tabulated and analyzed using multiple linear regression with SPSS. Based on the result of data analysis, there is a significant influence between tax service, penalties of late payment of tax, and penalties of tax reporting delay to obedience of UMKM Taxpayers using SAK ETAP in Batam. Based on the result of F test, it is obtained F table equal to 2,748 thus known F count (38,001)> F table (2,748) with Sig. (0,000) < 0.05, which means tax service (X1), late tax payment sanction (X2), and tax lateness reporting sanction (X3) affect jointly to Taxpayer compliance (Y) level. Viewed from R2 (R Square Change) obtained value 0.640. This means that the percentage of contribution of variable variable of tax service, sanction of late payment of tax and sanction of delay of tax reporting to variable of compliance level of UMKM using SAK ETAP is equal to 64%. While the remaining 36% influenced by other variables that are not included in this regression model, such as understanding Taxpayers, Taxpayers experience, income taxpayers, tax awareness systems, tax audits and others.Keywords: Tax service, tax payment late sanction, tax reporting late sanction, taxpayer obedience.